1998
DOI: 10.1021/ma981053s
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Bolaform Butadiyne 1-Glucosamide in Self-Assembled Nanoscale-Fiber Morphology

Abstract: Polymerization of constituent molecules in supramolecular self-assemblies 1 will provide stable covalent assemblies. In contrast to a number of studies on bilayer-membrane(BLM)-templated polymerization of diacetylenes, 2 only few studies have been reported for the polymerization in monolayer lipid membranes (MLMs) such as liposomes 3 or multi sheets. 4 Furthermore, the characteristics of the polymerized entity have been uncertain, owing to the fairly poor solubility of the products. Bolaamphiphiles, 5 unlike o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Photopolymerization of selfassembled fibers is an effective method to produce stable gels. [22][23][24][25][26][27][28][29] The enhancement of the thermal stability and durability of the self-assembled LC gels is essential for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Photopolymerization of selfassembled fibers is an effective method to produce stable gels. [22][23][24][25][26][27][28][29] The enhancement of the thermal stability and durability of the self-assembled LC gels is essential for practical applications.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Polymerization of constituent molecules in supramolecular selfassemblies 12 will provide stable covalent assemblies. In particular, polymerization of the LWMGs with diacetylene groups has been actively investigated, [13][14][15][16] as simple photoirradiation induces polymerization or oligomerization if they arrange and align in a good order. The connection of amide, aromatic or ionic groups to diyne motives through synthetic derivation enables one to attain appropriate molecular arrangement to the polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] For example, we previously reported that butadiyne 1-glucosamide connected bolaamphiphiles self-assemble to form nanofibers, and polymerization by photoirradiation causes the gelation of supramolecular networks in organic solvents. 16 In this synthesis, we always needed multistep derivation to attain the gelation.In the present work, we propose a new simple bola-type diacetylenic gelator. Inspired by the reports on gel-like systems of fatty acids and arginine, 24,25 we examined a salt of arginine and bola-type diacetylene diacid 10, 12-docosadiynedioic acid (DDA) for hydrogelation ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Possible molecular shapes and spatial arrangement of each functional group, and the local environment of solvophilic and solvophobic moieties allow us to produce a variety of discrete organic nanotubes, together with different types of self-assembly strategy. 2,11 We have been investigating the self-assembly behavior of synthetic amphiphilic molecules that append sugar, [12][13][14][15][16][17][18] peptide, [19][20][21] and nucleic acid moieties [22][23][24][25][26] as hydrophilic headgroups. 27 Those structural components in nature are wellknown to form diverse and multiple hydrogen-bond networks.…”
Section: Introductionmentioning
confidence: 99%